HOLINESS - Podgorski, Frank R (Journal of Dharma, 1983)
Holiness is the aim or goal of so many different people-contemplatives as well as activists, poets and artists, laity and monks, pastors and parishioners, women and men of vastly different creeds and cultures. But what is this "holiness" which both the Bible and the Bhagavad Gita proclaim "thousands set out in pursuit of" but yet paradoxically so few seem able to attain? Precisely what is the meaning of "holiness" attested to by the lives of so many different saints from so many different traditions? What leads a Catholic monk like Thomas Merton